The storyteller - Chee, Traci (2018)
The Book, the ancient, infinite codex of the past, present and future, tells of a prophecy that will plunge Kelanna in that bloody war, but it requires Archer. Sefia is determined to keep Archer out of the Guard's clutches and their plans for war between the Five Kingdoms: The Guard has already stolen her mother, her father, and her Aunt Nin. But escaping the Guard and the Book's prophecy is no easy task. As Sefia and Archer watch Kelanna start to crumble to the Guard's will, they must choose between their love and joining a war that just might tear them apart. -- adapted from jacket
830L
Keywords: Books and reading -- Juvenile fiction; Orphans -- Juvenile fiction; Prophecies -- Juvenile fiction; Young adult fiction; Action and adventure fiction; War fiction; Romance fiction; Fantasy fiction